Economic integration and network trade: A comparison of East Asia and the European Union - Son Thanh Nguyen; Yanrui Wu (Asian Development Bank Institute (ADBI), 2019)
The emergence of production networks has changed the structure of international trade, which a large share of intra-regional trade flows and the rising value of intermediate goods trade or network trade between countries within the same region reflect. While a production network exists in both East Asia and the European Union, the patterns could be different due to the differences in sociocultural, political, historical, and institutional factors between the two regions. This paper investigates and compares the pattern of network trade in East Asia and the European Union. It also explores how economic integration is related to the network trade pattern. The paper confirms that network trade in East Asia is more like a "network pattern," while that in the European Union follows a "hub-and-spoke pattern." At the global level, intermediate goods exports are more sensitive to trade barriers than total goods exports. A comparison between East Asia and the European Union shows that countries in East Asia have successfully reduced the service link costs. Despite the efforts that East Asia has directed towards export market diversification, the region is still more dependent on other regions' economic conditions than the European Union is. k
Keywords: F13; F14; F15; 330; production network; gravity model; European Union; East Asia; interdependence; remoteness; intermediate goods trade